Subacute Latissimus Dorsi Tendon Repair via a Single Posterior Incision - Thomas Spears DO, FAAOS; Patrick Luchini MD; Robert Nayfa MD; Peter Chang MD; Lance LeClere MD, FAAOS (Video Journal of Sports Medicine)
Background: This is a rare case of the surgical treatment of a subacute presentation of a latissimus dorsi tendon rupture via a posterior single-incision approach. Indications: The patient had extensive conservative, nonoperative treatment that failed, and ultimately a surgical intervention was required to return to his activities of daily living. Technique Description: The patient is positioned in a lateral decubitus position. A 10-cm incision is created along the posterior axillary fold. Sharp and blunt dissection is utilized to carefully mobilize the chronic tendon rupture. The tendon is captured with 2 suture tapes utilizing a locking Krackow whipstitch. The tendon footprint is identified between the pectoralis major and teres major. The insertion point is prepared with a Cobb to debride the soft tissue and decorticate the bone bed to optimize healing. Two endobuttons are loaded with the suture tapes and then passed through unicortical holes drilled in the tendon bed. Care is taken to ensure the 90° external rotation of the tendon is achieved. A tendon-slide technique is used to reduce the tendon to the humerus. Afterward, a free needle is used to pass 1 limb of the suture through the tendon before tying an additional knot for added fixation. Results: The patient was able to resume his activities of daily living without pain at the 4-month mark. Conclusions: After the failure of extensive nonoperative management, surgical treatment of a subacute complete rupture of the latissimus dorsi tendon via a single, posterior incision is an effective method of returning a patient to their painless activities of daily living. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.